Effects of Corruption and Development in Democratization - Efeoğlu, Rabia; Emsen, Ömer Selçuk (Bingöl Üniversitesi, 2020)
The aim of the study is to investigate the effect of the human development index, which is the indicator of economic development, and the corruption perception index, which is an indicator of corruption, on the level of democracy, using the panel ordered qualitative preference method with the data from the 2010-2018 period. While the widespread literature examines the growth and development effects of democracy or corruption, research has been designed in the theoretical perspective, especially in the light of arguments that development will trigger democratization. In this framework, since the dependent variable has ordered numbers, ordered logit model analysis which is one of the ordered qualitative preference models has been conducted for underdeveloped, developing and developed countries. According to the results of the research, it is determined that the improvements in both human development index and corruption perception index in underdeveloped and developed countries nourish democratization. On the other hand, while it is concluded that in developing countries, only the perception index of corruption was more effective at higher levels of democracy and is higher likely to affect the high level of democracy, it is observed that improvements in development did not favor democratization. At this point, the relationship between democratization and economic development in the form of a "u-curve" has been determined.

Çalışmanın amacı, ekonomik kalkınma göstergesi olan insani gelişme endeksi ile yolsuzluk göstergesi olan yolsuzluk algı endeksinin demokrasi düzeyine etkisi gelişmişlik düzeyi farklılık arz eden ülkeler için 2010-2018 dönemine ait veriler ile panel sıralı nitel tercih yöntemini kullanarak araştırmaktır. Yaygın literatür daha çok demokrasi veya yolsuzluğun büyüme ve kalkınma etkilerini incelerken, teorik perspektifte özellikle kalkınmanın demokratikleşmeyi tetikleyeceğine dair savlar eşliğinde araştırma kurgulanmıştır. Bu çerçevede bağımlı değişkenin sıra sayılar alması nedeniyle azgelişmiş, gelişmekte olan ve gelişmiş ülkeler için sıralı nitel tercih modellerinden sıralı logit model analizi yapılmıştır. Araştırma sonucuna göre az gelişmiş ve gelişmiş ülkelerde hem insani gelişme endeksi hem de yolsuzluk algı endeksindeki iyileşmelerin demokratikleşmeyi beslediği tespit edilmiştir. Buna karşılık gelişmekte olan ülkelerde ise yalnızca yolsuzluk algı endeksinin demokrasinin yüksek düzeylerinde daha etkili ve yüksek demokrasi düzeyini etkileme olasılığının daha yüksek olduğu sonucu elde edilirken, kalkınmadaki iyileşmelerin demokratikleşmeyi olumlulaştırmadığı gözlenmiştir. Bu noktada gelişmişlik düzeyi açısından demokratikleşme ile ekonomik gelişme arasında “u eğrisi” şeklinde bir ilişkinin varlığı tespit edilmiştir.
Keywords: Economics; Democracy; development; corruption; Demokrasi; kalkınma; yolsuzluk; Ekonomi